2019
DOI: 10.1371/journal.pone.0214924
|View full text |Cite
|
Sign up to set email alerts
|

Violence risk and mental disorders (VIORMED-2): A prospective multicenter study in Italy

Abstract: Background The management of mentally ill offenders in the community is one of the great challenges imposed on community psychiatry. Aim The aim of this study was to analyze the association between sociodemographic, clinical, and psychosocial factors and violent behavior in a sample of outpatients with severe mental disorders. Method This was a prospective cohort study with a baseline cross-sectional design used to provide a detailed analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…A previous study has also indicated that patients with a history of violent behavior have a high risk of exhibiting aggressive behavior again. 31 This result is in agreement with the findings of the present study.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…A previous study has also indicated that patients with a history of violent behavior have a high risk of exhibiting aggressive behavior again. 31 This result is in agreement with the findings of the present study.…”
Section: Resultssupporting
confidence: 94%
“…30 Patients with a history of violent behaviors have a relatively high risk of exhibiting violent behavior. 31 The violent behaviors of patients with schizophrenia include physical aggression, verbal aggression, anger, and hostility, which correlate with physiological changes in the brain. Sleep disorders may reduce emotional control, thereby increasing the frequency of violent behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is surprising that, although resources are probably more important in Italy than in other countries, staff still requires a larger number of doctors, psychologists and, to a lesser extent, of rehabilitation staff (such as Occupational Therapists, Educators or Rehabilitation Technicians). This likely reflects the emphasis in Italy on a healthcare model focused on medical treatment, rather than on an integrative approach [ 15 ]. In addition, in the region of Sardinia, where the study was conducted, a recent objective evaluation of staff numbers shows that there is an insufficient number of psychologists and rehabilitation workers [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in an Italian study, inpatients with a history of violence did not show at MOAS higher rates of aggressiveness compared to patients without such a history [85]. Interestingly, a second part of the study, exploring patients' behavior in the community, found that subjects with a lifetime history of violence engaged in more aggressive enactments than patients without [86]. The Authors speculated that when adequate treatment and management are available, a history of physical aggressiveness does not link with an increased risk of violence.…”
Section: History Of Aggressionsmentioning
confidence: 92%